Price Behaviour of 'Kusmi' Lac in Different Markets of West Bengal - Pal, Govind (Indian Forester, 2009)
The study was undertaken to analyse the price behaviour in terms of trend, seasonality and cycles in prices of lac in important primary, secondary and terminal markets of West Bengal. The secondary data on monthly average prices of lac at primary, secondary and terminal markets were collected for a period of 16 years spanning from 1990-91 to 2005-06. A positive trend has been shown in prices of kusmi lac during the study period which was statistically significant at one per cent probability level for all three levels of market. Growth rate of kusmi lac prices at growers, assembling centers, manufacturing centers and Kolkata market were found to be 10.16, 10.03, 9.06 and 7.72 per cent per annum, respectively. Increase in price at growers level and assembling centers were comparatively higher than that of price increase at manufacturing centers and Kolkata market. Only one peak of prices have been observed at growers and assembling centers level while two peaks of prices have been observed in case of manufacturing centers and Kolkata market. No regular cycles have been observed in the kusmi lac prices during the study period. Intra year price variation was more at growers and assembling centers level in comparison to manufacturing centers and Kolkata market. The seasonality in prices can be reduced by sustained production, production in diverse agroclimatic condition, primary processing of lac at village level and integration of lac production in various lac growing regions of the country.